Komposisi Jenis dan Adaptasi Vegetasi pada Areal Bekas Kebakaran pada Hutan Produksi Terbatas di Kota Kayuagung, Kabupaten Ogan Komering Ilir (OKI), Provinsi Sumatera Selatan - Lailan Syaufina; Aisyah Anggraini (Jurnal Silvikultur Tropika, 2021)
The research aimed to identifi changes in species composition and vegetation adaptation in burned forest production areas in Kayuagung, Ogan Komering Ilir district, South Sumatra Province. Forest fire in this area affected on spesies composition, whics is indicated by growth of seedling consistof gelam (Melaleuca leucadendron), tembesu (Fragraea fragrans), and perepat (Combretocarpus rotundus). On the other forest growth level found in unburned area including seedling, sapling poles, and tree. The dominant spesies growth from seedling to stand is meranti (Shorea balangeran), while the tree growth was consist of was meranti (Shorea balangeran), perepat (Combretocarpus rotundatus), tembesu (Fragraea fragrans), and jelutung (Dyera lowii), and was dominated by jelutung (Dyera lowii). Keywords: forest fire, forest production, Ogan Komering Ilir District, species composition, vegetation adaptation